Development of a four mecanum wheels omnidirectional mobile platform enabling remote motion control through a .NET graphical application or an inertial measurement unit - Arantes, Carlos Alberto Fernandes (2018)
Omnidirectional mobile platforms allow simultaneous translation and rotation, which leads to the optimization of their trajectories, a possible reduction of the distance traveled and, consequently, a reduction of the energetic consumption. This paper presents an omnidirectional mobile robot platform based on four Mecanum wheels, a graphical application running on .NET virtual machine which allows remote motion control and monitoring of several parameters of the platform, and an inertial remote control that uses an IMU (Inertial Measurement Unit) and an AHRS (Attitude and Heading Reference System) to set the movements of the platform.